2010
DOI: 10.1523/jneurosci.6178-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Germinal Zones of the Basal Ganglia But Not the Septum Generate GABAergic Interneurons for the Cortex

Abstract: Cortical interneurons originate from subpallial precursors and migrate into the cortex during development. Using genetic lineage tracing in transgenic mice we examine the contribution of two germinal zones, the septum and the lateral ganglionic eminence/caudal ganglionic eminence (LGE/CGE) to interneurons of the cortex. We find that the septal neuroepithelium does not generate interneurons for the neocortex. There is, however, clear migration of cells from the LGE/CGE to the cortex. Comparison of the dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
106
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(123 citation statements)
references
References 62 publications
16
106
1
Order By: Relevance
“…This might be due to the fact that many cells that are fated to become PV-expressing cells have not turned on the expression of this calcium-binding protein at P14, when we analyzed these experiments (Soriano et al, 1992). Third, the other regions containing Dbx1-expressing progenitors do not seem to produce GABAergic interneurons (Bielle et al, 2005;Rubin et al, 2010). Finally, it has been recently shown that a small fraction of PVϩ cortical interneurons derive from Shh-expressing cells in the subpallium (Flandin et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This might be due to the fact that many cells that are fated to become PV-expressing cells have not turned on the expression of this calcium-binding protein at P14, when we analyzed these experiments (Soriano et al, 1992). Third, the other regions containing Dbx1-expressing progenitors do not seem to produce GABAergic interneurons (Bielle et al, 2005;Rubin et al, 2010). Finally, it has been recently shown that a small fraction of PVϩ cortical interneurons derive from Shh-expressing cells in the subpallium (Flandin et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, recent experimental evidence indicates that the subpallial septum is not a source of cortical GABAergic interneurons (Rubin et al, 2010). In contrast, the POA has been previously shown to give rise to small populations of cortical and amygdalar GABAergic interneurons (Gelman et al, 2009;Hirata et al, 2009), which prompted us to analyze this region in more detail.…”
Section: The Embryonic Poa Is the Origin Of Dbx1-derived Cortical Intmentioning
confidence: 98%
See 2 more Smart Citations
“…In comparison, Nkx2.1 is expressed solely in the MGE, and the knockout exhibits only a 50% decrease in interneuron numbers [25,26]. More recently, the contribution of interneurons from the CGE has been examined by genetic fate mapping studies indicating that approximately 30% of cortical interneurons are produced within this area [27,28]. …”
Section: Cortical Interneuron Originmentioning
confidence: 99%